ADMINISTRATIVE AND LEGAL REGULATION OF DEPARTMENT OF STATE GUARD OF UKRAINE ACTIVITY IN THE COURSE OF STATE PROTECTION PERFORMANCE - Mykola, Mykytiuk (ВЕРХОВЕНСТВО ПРАВА, 2018)
The issue of ensuring senior offi cials security and protection of public authorities is very important and relevant nowadays. Planning a protective venue during the state guard provision has an agreed and regulated procedure aimed at achieving a single result. Taking it into consideration, the urgency of the issue of ensuring senior officials security is beyond doubt and requires further improvement in the activities of the Department of State Guard of Ukraine.